2019
DOI: 10.23889/ijpds.v4i1.1103
|View full text |Cite
|
Sign up to set email alerts
|

Sharing linked data sets for research: results from a deliberative public engagement event in British Columbia, Canada

Abstract: IntroductionResearch using linked data sets can lead to new insights and discoveries that positively impact society. However, the use of linked data raises concerns relating to illegitimate use, privacy, and security (e.g., identity theft, marginalization of some groups). It is increasingly recognized that the public needs to be consulted to develop data access systems that consider both the potential benefits and risks of research. Indeed, there are examples of data sharing projects being derailed because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
(41 reference statements)
4
25
0
Order By: Relevance
“…as an asset that should be used as long as their concerns related to privacy, commercial motives and other risks are addressed. [10][11][12][13] However, we cannot assume that this general but conditional public support for data-intensive health research extends to AI/ML for several reasons. Foremost, research has shown that the members of the general public have low understanding of AI in general, alongside AI-specific hopes and fears including loss of control of AI, ethical concerns and the potential negative impact of AI on work.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…as an asset that should be used as long as their concerns related to privacy, commercial motives and other risks are addressed. [10][11][12][13] However, we cannot assume that this general but conditional public support for data-intensive health research extends to AI/ML for several reasons. Foremost, research has shown that the members of the general public have low understanding of AI in general, alongside AI-specific hopes and fears including loss of control of AI, ethical concerns and the potential negative impact of AI on work.…”
Section: Open Accessmentioning
confidence: 99%
“…9 Previous studies exploring the public attitudes toward data-intensive health research in general, that is, without an AI/ML focus, found that most members of the mainstream public are supportive provided there are appropriate controls. [10][11][12][13] While underscoring the need to address the public's concerns, studies in Canada, the UK, the USA and other jurisdictions suggest that members of the mainstream public view health data…”
Section: Introductionmentioning
confidence: 99%
“…The international and Canadian research literature indicates that members of the general public are conditionally supportive of data-intensive health research provided that their concerns related to privacy, security and commercial motives are addressed [9,33,[40][41][42][43][44]. It is our view that governance is the best way to ensure that data trusts meet all legal requirements AND align with social licence, using the term governance to refer to the "locus of accountability for decision-making" in contrast with management which "involves making and implementing decisions" [45].…”
Section: Requirement 2: Governance -Four (4) Min Specsmentioning
confidence: 99%
“…We believe that achieving effective proportionate governance of health data [19] requires authentic public and patient involvement that follows accepted principles such as inclusiveness, two-way communication and transparency [20]. There is a growing body of research evidence about public expectations around social licence and acceptable data uses of health data [21][22][23][24], and increasing commitment from many institutions to include the public in one way or another to inform or influence policies [7][8][9][10], but we have not yet implemented or operationalized the principles and ideas presented in the research literature at scale. One approach, presented here, is to create some standardized communications that distinguish between different uses of health data to ensure that members of the public do not confuse, or group together, commercial revenue-generating uses with public sector data-intensive health research.…”
mentioning
confidence: 99%
“…The international research literature describes general but conditional public support for dataintensive health research. Qualitative studies indicate that members of the public view health data as an asset that should be used as long as there is a public benefit and their concerns related to privacy, commercial motives and other risks are addressed [21][22][23][24]. The Wellcome Trust, Ipsos Mori One-Way Mirror Report identifies four 'key tests' for public acceptability of commercial use of health data [24]:…”
mentioning
confidence: 99%